UNI-Event: Student’s Events and Activities Mobile Application - Mohamad Zahir, Danieal Hazziq (IRC, 2020)
An event can be defined as a thing that happens or taken place at a specific location during certain period of time which can be a planned public or social occasion, or it can be competition that can be broken down into several particular contests, based on the Oxford dictionary. People around the world used events as a concept to gather in order for them to accomplish their desired goal together. University is one of the places that have a high number of events conducted in a definite period of time, specifically during the on semester, where there are lots of individuals, clubs and organizations who handles events with their goals in mind. As for the perspective of the students in the university, those events should be considered to be their co-curriculum activities as it provides the students a different content and experience of learning when compared to standard lecture session. Now days, there are less variation of students who involved in these co-curricular activities as the same group of people have the higher tendency to get involved in the events. This paper aims to conduct an analysis regarding the involvement of students in co-curricular activities in university through the existing system of joining the events. By analyzing the existing system of involving into events will support the purpose of this project in which developing a new system that able to solve the existing problems in order to make the process became more efficient and interactive. Co-curricular activities are very important for the students to get involve in because there are lots of benefits that will come alongside the process, such as improvement in soft skill. Hence, the number of students involve in the events and activities should be increasing through the implementation of the new system. The existing system analyzed is specifically in University Technology PETRONAS and may differ with the other university where the culture and approach are different. The main concept explained in this paper about differentiation of the existing system and new system should be able to apply to all of the students across the board as the more efficient way of executing things will always be more delighting.